Pricing on project works abroad - Shumak, L.V.; Zapiechna , Y. О. (Ways to Improve Construction Efficiency, 2020)
The article presents the analysis results of the literature of foreign experience in the field of design in the development of design and estimate documentation, in particular the determination of the design work cost. The current pricing mechanism in different countries is analyzed. Scientific works of foreign experts on the researched problem of estimate rationing, development and implementation of standards, different approaches to substantiation of construction cost and methodical bases of pricing of project production are a theoretical basis of research. Contradictions with the requirements of normative documents in force abroad, which arise during design, have been revealed. Possible changes that could be made to the standards on the basis of domestic and foreign research and design experience are indicated. The generalization of foreign experience indicates the presence of both negative and positive aspects in the field of design, as well as some areas for improving the work of our Ukrainian designers. The analysis of the estimated cost of design work formation in accordance with international practice shows that in the Ukrainian practice of development of estimated rationing in the direction of determining the cost of design work is given insufficient attention. A review of foreign experience in the field of design solutions is very rare in Ukrainian publications and remains the work of specialists of a narrow profile. It is necessary to ensure a radical improvement of the system of estimated standards, increasing their feasibility study. Price guarantees for the integrated use of the principles of commercial calculation should be created on this basis. In international design practice, a lot of attention is paid to the level of information messages in special periodicals. These general analytical views on the existence abroad of a system of estimated rationing, labor costs at the design stage give the impression that this area is constantly paid attention to by foreign experts. This indicates a periodic review of the economic component in the design. However, this issue remains open and relevant to this day.